2023
DOI: 10.3389/fcimb.2023.1227581
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the pulmonary microbiota in patients with mild and severe pulmonary infection

Danting Zhan,
Dan Li,
Ke Yuan
et al.

Abstract: BackgroundLung infection is a global health problem associated with high morbidity and mortality and increasing rates of hospitalization. The correlation between pulmonary microecology and infection severity remains unclear. Therefore, the purpose of this study was to investigate the differences in lung microecology and potential biomarkers in patients with mild and severe pulmonary infection.MethodPatients with pulmonary infection or suspected infection were divided into the mild group (140 cases) and the sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the disease condition, the presence and abundance of pathogens in the lung are not consistently mirrored in the oropharynx, underlining the importance of direct sampling of the lower airway with bronchoalveolar lavage (BALF) in investigating lung microbiota [23]. Several studies comparing diseased versus healthy lungs found significant differences in community composition, with the disease condition being associated with loss of bacteria diversity or with a dominance of a single taxon or small group of taxa [24][25][26]. Microbial dysbiosis characterizes various lung diseases, in which a reduced microbial diversity has been also associated with disease progression [7,[27][28][29].…”
Section: Lung Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…In the disease condition, the presence and abundance of pathogens in the lung are not consistently mirrored in the oropharynx, underlining the importance of direct sampling of the lower airway with bronchoalveolar lavage (BALF) in investigating lung microbiota [23]. Several studies comparing diseased versus healthy lungs found significant differences in community composition, with the disease condition being associated with loss of bacteria diversity or with a dominance of a single taxon or small group of taxa [24][25][26]. Microbial dysbiosis characterizes various lung diseases, in which a reduced microbial diversity has been also associated with disease progression [7,[27][28][29].…”
Section: Lung Microbiotamentioning
confidence: 99%
“…A recent work describes a significant increased viral replication in severe pulmonary infections, and a difference in microbial interactions between patients with bland and severe disease, especially the association between the common pathogenic bacteria and Rothia [26]. The high mortality risk due to influenza is mostly attributed to secondary bacterial infections.…”
Section: Lung Microbiota Modifications During Respiratory Infectionsmentioning
confidence: 99%
“…The lung microbiota plays a vital role in maintaining respiratory health and influencing the severity of lower respiratory tract diseases ( Fenn et al., 2022 ). Although studies have explored the characteristics of lung microbiota across different severity levels of lung infections using metagenomics ( Zhan et al., 2023 ), multidimensional analysis of lung microbiota characteristics remains limited.…”
Section: Introductionmentioning
confidence: 99%